Developing Creative Tourism Activity Patterns and Routing Tourist Routes, Touching the Charms of the Old City Lifestyle Phra Nakhon Si Ayutthaya Province - Akkarapatkamchai, Phawat; Phuanpoh, Yanisa; Chantanee, Metharat; Mahasumran, Worapapha; Kludcharoen, Marut (Rajapark Journal, 2023)
This research was purposed to study 1) Potential and tourism behavior in tourist attractions 2) Create media to publicize activities and travel routes and 3) to develop creative forms, organize activities and travel routes to experience the charm of the old city lifestyle Phra Nakhon Si Ayutthaya Province. This is mixed method research, The sampling consisted of tourists, community leaders/ network partners 400. It used a questionnaire, an in-depth interview. The statistics were data analysis, percentage, mean, standard deviation, t-test statistics. The result found that 1) Most were female, aged 40-49 years, marital status, lower secondary education, agriculture occupation with income 15,001-30,000 baht 2) The tourist behavior of tourists found that most by private cars, travel time Monday – Friday Travel by setting your own travel program 3) Community tourism potential level at a high level, the level of creating tourism public and the level of creativity in organizing activities and tourism routes in terms of forms of creative activities, the overall average is at a high level.